2021
DOI: 10.3390/ncrna7030058
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Coding RNA Journal Club: Highlights on Recent Papers—9

Abstract: We are delighted to share with you our ninth Journal Club and highlight some of the most interesting papers published recently [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…If a circRNA has a negative correlation with a miRNA and a positive correlation with its target mRNA, this circRNA is always considered to act as a miRNA sponge. Nevertheless, it has recently been demonstrated that this correlation may result from the co-expression or mutual exclusion of subpopulations [ 85 , 86 ]. Bulk tissues are typically composed of a heterogeneous mixture of cell types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a circRNA has a negative correlation with a miRNA and a positive correlation with its target mRNA, this circRNA is always considered to act as a miRNA sponge. Nevertheless, it has recently been demonstrated that this correlation may result from the co-expression or mutual exclusion of subpopulations [ 85 , 86 ]. Bulk tissues are typically composed of a heterogeneous mixture of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, colon and prostate tumor tissues often contain uneven proportions of muscle cells, which are known to be rich in circRNAs [ 99 ]. Consequently, the discrepancy in muscle cell content between different samples may give rise to an artifactual bias in circRNA expression [ 85 , 86 , 98 , 99 ]. Similarly, lncRNA expression is also cell-specific, which means that the analysis of lncRNA/circRNA expression and function using large tissue samples, such as tumor and non-tumor adjacent specimens, may result in erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect evidence for the “sponge” function is strong and is consistent with criteria presented in the non-coding RNA Journal Club—9, abstract, “5. No Co-expression, No Sponging”, highlighted by Laura Poliseno [ 5 ].…”
Section: The Human Long Intergenic Non-coding Rna Gene Linc-ur-ub Simple Origins But Complex Functionsmentioning
confidence: 99%